Towards transformative fiqh education: a deep learning pedagogical approach in the digital era - Sari, Hesti Indah; Salim, Agus (UIR Press, 2026)
The persistence of teacher-centered and memorization-oriented approaches in fiqh education has limited students’ conceptual understanding and critical engagement with Islamic legal knowledge, particularly within contemporary digital contexts. This study aims to examine the implementation of a deep learning pedagogical approach in fiqh instruction at the Madrasah Tsanawiyah level and its impact on students’ conceptual understanding and critical thinking skills. Employing a qualitative case study design, data were collected through classroom observations, in-depth interviews, and document analysis involving teachers and students at madrasah tsanawiyah. The findings reveal that deep learning fosters an interactive, contextual, and student-centered learning environment, significantly enhancing students’ ability to analyze legal sources, relate fiqh concepts to everyday practices, and engage in collaborative reasoning. Despite these positive outcomes, the study is constrained by limited infrastructure, the absence of quantitative validation, and varying levels of teacher readiness. These limitations suggest the need for institutional support and professional development to sustain pedagogical transformation. The study implies that integrating deep learning with Islamic educational values can strengthen both cognitive and ethical dimensions of learning. The novelty of this research lies in conceptualizing deep learning as a holistic Islamic pedagogical framework that integrates case-based inquiry, digital literacy, and value internalization in fiqh education